1993
DOI: 10.1021/ic00066a009
|View full text |Cite
|
Sign up to set email alerts
|

Structure of copper(II) ethylenediamine complexes in aqueous and neat ethylenediamine solutions and solvent-exchange kinetics of the copper(II) ion in ethylenediamine as studied by EXAFS and NMR methods

Abstract: The structures of copper(II) complexes with ethylenediamine (en) in aqueous and neat ethylenediamine solutions have been determined by the EXAFS (extended X-ray absorption fine structure) method. The copper(II) ion in en has an axially elongated octahedral structure with three en molecules. The Cu-N bond lengths in the four equatorial and two axial positions are 204(1) and 239(2) pm, respectively. The dynamic exchange reaction between en molecules in the bulk and en molecules bound to the copper(II) ion has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 0 publications
2
48
0
Order By: Relevance
“…The fitted coordination number (CN), bond length (R), Debye-Waller factors (r 2 ), threshold energy shift (DE 0 ), and residue (R residue ) for all the four P-Amine-b-Cu from the analysis are given in Table 2. It can be found that the Cu-C distance (distance between Cu and neighboring C atoms) was in the range of 2.84-2.87 Å, in good agreement with the results reported in the literatures [36][37][38]. In addition, the r 2 values for the Cu-C bonds were all larger than those for Cu-O or Cu-N.…”
Section: Coordination Structure and Coordination Number For Copper Iosupporting
confidence: 90%
See 1 more Smart Citation
“…The fitted coordination number (CN), bond length (R), Debye-Waller factors (r 2 ), threshold energy shift (DE 0 ), and residue (R residue ) for all the four P-Amine-b-Cu from the analysis are given in Table 2. It can be found that the Cu-C distance (distance between Cu and neighboring C atoms) was in the range of 2.84-2.87 Å, in good agreement with the results reported in the literatures [36][37][38]. In addition, the r 2 values for the Cu-C bonds were all larger than those for Cu-O or Cu-N.…”
Section: Coordination Structure and Coordination Number For Copper Iosupporting
confidence: 90%
“…In an effort to solve this problem, a data fit approach was used to match the bond length of the Cu-O and Cu-N, respectively. According to the literature, the coordination bond lengths of Cu-O and Cu-N were mainly in the range of 1.90-1.94 and 2.00-2.04 Å, respectively [33][34][35][36][37][38]. Therefore, the constraint of 1.90-1.94 Å was applied to Cu-O bonds and that of 2.00-2.04 Å was applied to Cu-N bonds in this study.…”
Section: Coordination Structure and Coordination Number For Copper Iomentioning
confidence: 95%
“…Recently, the studies of the solvation structure of the first-row transition metal(II) ions in some non-aqueous solvents have pointed out that the bulkiness of solvent molecules can reduce the solvation number of a metal(II) ion in some instances, due to the large steric repulsion between the bound solvent molecules in the first coordination sphere. [2][3][4][5][6][7][8][9] For example, the coordination number of Mn(II), Fe(II), and Ni(II) ions is 5 and that of Co(II), Cu(II), and Zn(II) ions is 4 in a bulky solvent of 1,1,3,3-tetramethylurea (TMU).2 A similar characteristic is also observed in the bulkier hexamethylphosphoric triamide (HMPA) solvent. 3 It should be noted that the molar volume of a solvent is not a measure of the bulkiness of coordinated solvent molecules.…”
mentioning
confidence: 97%
“…Ethylenediamine is a diamine with a small size which can form a complex with Cu 2+ [49] and hence block it so no more ligands can bind to it. So it is expected that it can easily approach and form a complex with it.…”
Section: Introductionmentioning
confidence: 99%